METHOD OF QUANTIFICATION OF RISK OF TECHNICAL SYSTEM (Transport systems and technologies, 2018)
Risk analysis is important on dangerous man-made objects due to the need to provide anecdotal safety and prevent accidents. It involves obtaining quantitative estimates of the potential danger of man-made objects and recommendations for its reduction through the implementation of appropriate engineering, technical and organizational measures. The method of quantitative analysis of the risk of accidents on man-made objects is considered the basis of the methodology for determining the risks of man-made objects and modeling the processes of occurrence and development of accidents. We introduced the application of a mathematical probabilistic model for predicting individual and social risk using an automated computer system. According to the Cabinet of Ministers of Ukraine "On the identification and declaration of safety of high-risk objects", the declaration of dangerous industrial activities is carried out, an important direction of implementation of which is the development of a method for quantitative analysis of the risk of accidents on man-made objects. The method of risk analysis allows predicting the distribution of hazardous areas in the event of an accident, the distribution of workers at the facility at the accident (probabilistic), and the individual and social risks for workers in the production area (regularity). Risk forecasting allows employees to be informed about risks, improve the effectiveness of the personnel protection measures being developed in the event of an accident, and prevent the negative consequences of accidents.
Keywords: man-made object, source of danger, probability, individual risk, social risk, risk assessment, risk forecasting